Balanced Nutrition Education for Class 3 SDN Cikeruh I Jatinangor District, Sumedang Regency - Hendrawati Hendrawati; Udin Rosidin, Iceu Amira; Sukma Senjaya (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Nutritional problems in early childhood are very vulnerable to children's health development. In general, a person's nutrition is determined by behavior and habits carried out since childhood. If the knowledge and education provided is appropriate, then nutritional problems which are currently becoming urgent problems, such as stunting, wasting and underweight can be prevented and addressed properly. Nutritional status is an illustration of the adequacy of the body's metabolic system's needs in carrying out its functions. There are two possible causes of nutritional problems that occur in children, namely lack and excess nutrition. Early childhood is an easy time to implement and teach about good nutrition and can be implemented well because this is something they forget to monitor. The aim of this education is that students understand good nutrition and are able to implement the importance of balanced nutrition. The way to socialize this educational activity can be done through lectures, questions and answers, simulations, and watching videos at school. An interactive and informative approach is very important to make participants actively involved in the learning process. The number of participants who took part in this activity was 28 students, both male and female. The results of this educational activity were measured by assessing the participants' knowledge before and after the education. The previous score was only 58 and after the education it increased to 88, where there was an increase in knowledge of 30 points after the activity. with this social action activity to reduce the prevalence of stunting which is detrimental to children's future because balanced nutrition plays an important role in the growth and development, health and welfare of children in the future. Teachers and people are expected to monitor the food consumed by students and their children so that children are healthy and develop according to their age and become good successors of the nation.